A mutational analysis of the interaction between FliG and FliM, two components of the flagellar motor of Escherichia coli. - Marykwas, D L (1996)
The motor that drives the flagellar filament of Escherichia coli contains three "switch" proteins (FliG, FliM, and FliN) that together determine the direction of rotation. Each is required, in addition, for flagellar assembly and for torque generation. These proteins interact in the Saccharomyces cerevisiae two-hybrid system: FliG interacts with FliM, FliM interacts with itself, and FliM interacts with FliN. The interaction between FliG and FliM has been subjected to mutational analysis. FliG (fused to the GAL4 DNA-binding domain) and FliM (fused to a GAL4 transcription activation domain) together activate transcription of a GAL4-dependent lacZ reporter gene. DNA encoding FliG was mutagenized by error-prone amplification with Taq polymerase, mutant fliG genes were cloned (as DNA-binding domain-fliG gene fusions) in S. cerevisiae by gap repair of plasmid DNA, and mutants exhibiting an interaction defect were isolated in a two-hybrid screen. The mutations were each mapped to the first, second, or last third of the fliG gene by multifragment cloning in vivo and then identified by DNA sequencing. In this way, we identified 18 interaction-defective and 15 silent (non-interaction-defective) fliG mutations. Several residues within the middle third of FliG are strongly involved in the FliG-FliM interaction, while residues near the N or C terminus are less important. This clustering, when compared with results of previous studies, suggests that the FliG-FliM interaction plays a central role in switching.